FAKTOR-FAKTOR YANG MENYEBABKAN ANAK TIDAK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI TAHUN 2018 DI KECAMATAN KUOK KABUPATEN KAMPAR - Lena Lena; Zahirman Zahirman; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research was motivated by many children who did not continue their tertiary education in Kuok District, Kampar Regency. It is affected by both internal factors and external factors. The internal factors are such as physical, psychological, and fatigue. And the external factors are such as family, school, and community. The formulation of the problem in this study is